2014
DOI: 10.5301/jva.5000225
|View full text |Cite
|
Sign up to set email alerts
|

Flushing the Central Venous Catheter: Is Heparin Necessary?

Abstract: There is no evidence of a different effectiveness between heparin flushing and normal saline or other solutions in reducing catheter occlusions. Due to the little and inconclusive evidence available in this field, further studies might be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
(53 reference statements)
3
31
0
3
Order By: Relevance
“…The result of the first study (network meta-analysis) was no marked difference, when comparing adult patients with NS vs HS or other solutions in the flushing of CVCs [33]. The second study, consistent with results of previous research, found that HS was not more effective than NS in reducing catheter occlusion when analysed in three different areas (participant, catheter and line access) [18].…”
Section: Discussionsupporting
confidence: 54%
“…The result of the first study (network meta-analysis) was no marked difference, when comparing adult patients with NS vs HS or other solutions in the flushing of CVCs [33]. The second study, consistent with results of previous research, found that HS was not more effective than NS in reducing catheter occlusion when analysed in three different areas (participant, catheter and line access) [18].…”
Section: Discussionsupporting
confidence: 54%
“…Historically, heparin solution has been the most commonly used method to maintain catheter patency, dating back to the 1970s (1) . However, this practice seems to have concealed its negative effects (1,3) , of which we can highlight the iatrogenic effects of the drug itself, such as thrombocytopenia.…”
Section: Introductionmentioning
confidence: 98%
“…Although on the one hand its use has enabled therapeutic advances, it has also led to the origin of various associated risks, of which infection and catheter obstruction (1)(2)(3)(4) can be highlighted; factors contributing to an increase of hospital internalizations, morbidity and hospitalization costs (4) . For these reasons, CVC handling, maintenance and optimization is complicit to the predominant value of care, where nurses must gather a body of knowledge and skills to ensure proper handling of the CVC (5) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations